An efficient multiple meta-model-based global optimization method for computationally intensive problems. (February 2021) - Gu, Jichao
Highlights: An efficient multiple meta-model-based global optimization (EMMGO) algorithm is developed. The design space is divided into an important region and a remaining region: 21 new trial points are selected in each iteration. Multiple searches improve efficiency and robustness of the search process EMMGO outperforms other state-of-the-art algorithms in six mathematical optimization problems and a real structural optimization problem. Abstract: Present metamodel based global optimization algorithms usually build an evolving metamodel using initial and updated sample points to speed up the search of the global optimum. In this research, we proposed an efficient and robust multiple meta-model-based global optimization method (EMMGO). The EMMGO starts with two different sets of initial points and two different sets of evolving metamodels to search the design space. One evolving set of meta-models are updated using all sample points at each iteration of the search. The other set of meta-models are constructed using the sample points without the set of points which contains the initial best. These two sets of evolving meta-models consist of three components: radial basis function, Kriging and quadratic function. In the iterative search process, an important region, likely to contain the global optimum, is first identified using a few expensive points, and the search of the global optimum is conducted over this region using both of the two sets of metamodels. Meanwhile, the evolving meta-models fitted using all obtained points are used in the search over the other area and the entire design space to avoid missing the global optimum. The new EMMGO algorithm is tested using several commonly-used benchmark functions. The search efficiency of the new algorithm is also illustrated by solving a practical, computationally intensive global optimization problem in designing a lightweight vehicle, employing finite element analysis and simulation. The results from efficient global optimization and multiple metamodels based design space differentiation are provided for search performance comparison.